Use of particulate surrogates for assessing microbial mobility in subsurface ecosystems - Sinreich, Michael; Flynn, Raymond; Zopfi, Jakob (My University, 2009)
Mass fluxes from the ground surface can play a vital role in influencing groundwater ecosystems. Rates of delivery may influence intact ecosystem composition, while fluxes of substances associated with anthropogenic activity may critically alter the functioning of associated microbial assemblages. Field-based tracing experiments offer a valuable means of understanding mass transport rates and mechanisms, particularly in complex heterogeneous epikarst systems overlying vulnerable fissured aquifers. A short-term tracer experiment monitoring solute and particle tracer concentrations after they passed through a 10-m-thick sequence of limestone, capped by a thin soil, revealed rapid travel times and variable attenuation rates for the substances employed. Results demonstrated that particle tracers have shorter average travel times and can reach the subsurface in higher concentrations and over shorter times than non-reactive solutes. High recovery rates for the bacterial tracer Ralstonia eutropha H16 contrasted strongly with those of similarly sized fluorescent polystyrene microspheres, highlighting the importance of physico-chemical surface characteristics of particle tracers. Complementary laboratory batch experiments examined the role played by organic and inorganic soil/rock surfaces on particle tracer attenuation. Findings suggest that biofilms may significantly promote transport of particulate material below ground, i.e., the delivery of allochthonous microorganisms to karst groundwater.
Keywords: Karst; Vadose zone; Bacterial transport; Tracer tests; Switzerland